BEHAVIORAL ACTIVATION DAN TERAPI KELUARGA PADA PASIEN PSIKOAFEKTIF TIPE DEPRESI - Grace Latuheru (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
Schizoaffective disorder is a disorder that has the characteristics of schizophrenia and affective or mood disorders. Schizoaffective disorder is an illness in which persistent psychotic symptoms, such as hallucinations or delusions, occur together with a mood disorder such as depressive, manic, or mixed episodes. As a result, an individual with this disorder will be unable to carry out their daily activities. Therefore, behavior modification is carried out to reduce these behavioral symptoms. In this study, researchers used a research method, namely the single subject experimental method, by behavioral activation to activate alternative behaviors. The subject in this study is 1 person who showed psychoaffective symptoms. The subject is aged 26 years. The sampling of the subject is based on symptoms obtained from interviews and observations with medical record data. The data collection techniques used observation, interviews, and psychological tests (WAIS, GRAPHICS, TAT, WWQ). The interventions carried out were behavior modification using behavioral activation to train subject independence and family therapy as education in providing treatment to the subject. After giving psychoeducation, the family understood what to do and what not to do in dealing with the client. Additionally, the family was aware of their negligence too. They also understood how to deal with and control the client. After providing Behavioral Activation, the client perceived that they have activities that must be done every day. They believed that they have responsibility for every activity. They became more organized and less confused at home.